Bakti Sosial Pengobatan Gratis dan Penyuluhan Pengetahuan Tentang Tanaman Obat Keluarga (TOGA) Di Sekolah Tanjung Pura Langkat - Suryani, Monica; Jon Kenedy Marpaung; Suharyanisa Suharyanisa; Mestika Lumbantoruan (Universitas Kristen Indonesia Toraja, 2023)
Family medicinal plants (abbreviated as TOGA) are home-cultivated plants that have medicinal properties. A family medicine garden is essentially a plot of land, whether in the yard, garden or field, which is used to cultivate medicinal plants in order to meet the family's need for medicines. The purpose of this service activity is to provide social services for free medical treatment and dissemination of knowledge about family medicinal plants (TOGA) at the Tanjung Pura Langkat school. This method of activity involved lecturers at the Sari Mutiara Indonesia University, the regent, the sub-district head and the people of Langkat. The result of this activity is that the community service team hopes that the community can get free medication and knowledge about family medicinal plants. Based on the results of the Community Service activities carried out, these activities went well and the community received treatment and received knowledge about family medicinal plants so that the community could improve their health.